DESAIN PONDASI TELAPAK BERDASARKAN UJI CPT DI DAERAH KUTA, BALI - I Gusti Ngurah Putu Dharmayasa; Dewa Ayu Nyoman Ardi Utami (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2018)
Rapid exploitation of land in Bali, especially in the Kuta area due to the development of tourism, makes it difficult to obtain land and the price is expensive, so that the available land should be maximally used. The impact of maximum land use is the influence on the structure of the building to be built. The building structure component which affected is the foundation. Due to the very tight density of the building, it is necessary to consider the shallow foundation design that was widely used in the Kuta area to avoid structural failure, so that the designed buildings could stand safely. If the foundation receives an eccentric load, it will be very dangerous for the building if it does not fit between the load received and the size of the foundation being made. This would be disastrous in case of a construction failure due to a design error, so it was desirable to do research on the design of the shallow foundation with an eccentric load on the buildings located in the Kuta tourist area to obtain an adequate shallow foundation design based on the soil data and structural load will be built. To analyze the bearing capacity of the soil and the design of the foundation, it is necessary to provide data from land investigation in the field. Land investigation in the field was conducted with CPT. Based on CPT results obtained hard layer soil at a depth of 2 - 2.2 m. The shallow foundation was planned at a depth of 1.6 meters and the foot size of 1.5 m x 1.5 m with minimum allowable bearing capacity (qa) was 20,99 t/m2. The result of analysis of 2-storey building structure resulted axial load (P) was 25750.88 kg, moment about the X axis (Mx) was 2529.70 kg m and moment about the Y axis (My) was 2929.65 kg m. The dimensions of the footing are 1.5 m x 1.5 m and the thickness (t) was 580 mm. Minimum pressure on foundation (q min) was 6.238 t/m2 and the maximum pressure on foundation (q max) was 17.583 t/m2. For bending reinforcement was used 19 mm diameter reinforcing steel with a distance of 150 mm.